Branch and canopy data from Linnaeus University trial site with uneven-sized Norway spruce in Simontorp - Fagerberg, Nils (Linnaeus University, 2023)
Branch and crown data for the living part of the tree crown in an uneven-sized Norway spruce dominated stand in northern Scania, Sweden. The objective is to create a model for knot size depending on the local competition status around of the individual tree. The data contains information on maximum branch length at 30 cm intervals along the entire tree height. A smaller part of the observations are linked to branch diameter. Tree-level data includes growth, tree position, and crown data. Data collection between 2016 and 2018 as part of a PhD project at Linnaeus University, Dept. of Forestry and Wood Technology. The data collection site is marked in the field.

The file "Combined adjusted h0a clean V2.csv" contains data with 3,803 height section observations from Simontorp's sample plot distributed on 80 Norway spruce trees. The data represent branch data from the living part of the crown. 58 variables, i.a. horizontal branch length, branch diameter, whorl height, tree diameter and tree position. The variables are explained in "Branch data designations.xlsx".

The file "Branchdata 20-12-03.csv" contains data from 4,089 branch and branch rotation observations from the same plot, with measurements up to 5.5m stem height. 25 variables, including branch diameter and branch position on the stem. An explanation of the variables can be found in "Designations flat data ver4.xlsx".

There is also a central file "N1b_all_sep.xlsx" which contains data for tree species, tree diameter and tree position for all trees >6 cm dbh in the sample plot (see sheet "Simontorp"). Explanations are found in a separate sheet in the same data file, as well as in the documentation file "Plantor och ståndort.docx". However, these two files are published under another entry in SND (2021-174 Tree growth and position data from Linnaeus University's uneven-sized plots, linked from this entry) and can be downloaded from there.

Gren och krondata för den levande delen av trädkronan i ett skiktat granbestånd i norra Skåne. Syftet vara att skapa en modell för kviststorlek beroende av det individuella trädets konkurrenssituation. Datan innehåller information om max grenlängd med 30 cm intervall längs hela trädhöjden. En mindre del av observationerna är kopplade till grendiameter. Data på trädnivå innehåller tillväxt, trädpositioner och krondata. Datainsamling mellan 2016 och 2018 som en del av ett doktorandprojekt på Linnéuniversitetet, inst. för skog och träteknik. Ytan är markerad i fält.

Filen "Combined adjusted h0a clean V2.csv" innehåller data med 3 803 höjdsektionsobservationer från Simontorps provyta fördelade på 80 granar. Uppgifterna representerar grendata från den levande delen av kronan. 58 variabler, bl.a. horisontell grenlängd, grendiameter, grenvarvshöjd, träddiameter och trädposition. Förklaring av variablerna finns i "Branch data designations.xlsx".

Filen "Branchdata 20-12-03.csv" innehåller data med 4 089 gren- och grenvarvsobservationer från samma yta, med mätningar upp till 5,5m stamhöjd. 25 variabler, bl.a grendiameter och grenposition på stammen. Förklaring av variablerna finns i "Designations flat data ver4.xlsx".

Det finns även en central fil "N1b_all_sep.xlsx" som innehåller trädart, träddiameter och trädposition för samtliga träd >6 cm dbh på provytan (see flik "Simontorp). Kodförklaringar finns i egen flik i datafilen, samt i dokumentationsfilen "Plantor och ståndort.docx". Dessa två filer är dock publicerade under en annan post i SND (2021-174 Träddata för tillväxt och positioner från Linnéuniversitetets skiktade provytor, länkad från denna post) och kan laddas ner därifrån.
Gren- och krondata från Linnéuniversitetets provyta med skiktad granskog i Simontorp
Keywords: forest exploitation; skogsbruk; tree; träd; Land use; Markanvändning; Statistical units; Statistiska enheter; timber growing; trädodling; Norway spruce; gran (art); tree stand; trädbestånd; branch size; grenstorlek; tree positions; trädpositioner; uneven-sized stand; skiktat bestånd; knot size; kviststorlek; Picea abies; Forest Science; Skogsvetenskap; Farming; Areella näringar; Environment; Miljö